Hubungan Kontrol Diri Dengan Disiplin Siswa Kelas XI Perhotelan SMK N 9 Padang - Boby Delfiansyah; Menrisal (JURNAL INOVASI EDUKASI, 2024)
This research aims to determine the relationship between Self-Control and Discipline in class XI Hospitality Students at SMK N 9 Padang. The type of research used in this Research is Quantitative. The Research Population was 179 People, with a Sample of 64 People taken using a Proportional Random Sampling Technique. This research examines the relationship between Self-Control and Student Discipline. The Instrument used in Data Collection in this Research was a Questionnaire prepared according to the Likert Scale model. Data Analysis was carried out using Statistical programs on the computer SPSS 16 and Microsoft Excel 2016. Based on the Results of the Analysis, it was found that the r value was 0.737 with an Alpha level of 0.05 because the r value was greater than Alpha (0.737 > 0.05) so there was a significant positive relationship. Between Self-Control and Discipline of Class XI Hospitality Students at SMK N 9 Padang.